State-based limited license pathways: implications for graduate medical education, patient safety, and the U.S. physician workforce - Madison R McCraney; Casey C Glymph; Jaclyn M Hall; Christopher R Cogle (Academic Medicine, 2026)
Abstract Each year a competitive pool of over 52,000 applicants vying for 40,000 available residency positions in the United States leaves thousands of qualified graduates, particularly international medical graduates, without residency placements. At the same time, the nation faces a projected physician shortage of up to 86,000 by 2036, deepening concerns about health care access in underserved and rural communities. In response, several states have introduced limited license pathways, which allow unmatched medical school graduates who have passed licensing exams to practice under supervision without completing a residency program. As of May 2026, 12 states have implemented limited license pathways, signaling a shift in how physician readiness and medical licensure are defined in the United States. A comparative analysis of Canadian and U.S. state models offers insights into pathway variations and deficiencies in standardized oversight and longitudinal assessment of limited licensees. While these pathways aim to reengage unmatched graduates and alleviate workforce shortages, they raise critical concerns about the erosion of educational standards, patient safety, and professional development. This article examines the ethical and educational risks of these parallel license pathways and proposes 4 foundational components for minimum standards—educational oversight and quality standards, transparency and patient disclosure, career development support, and policy framing and communication. The academic medicine community has both the expertise and responsibility to lead a coordinated response, engaging national medical education organizations and state lawmakers, to ensure these licensure innovations enhance rather than compromise the integrity of the physician workforce pipeline and do not come at the cost of physician competence or patient safety.